Pengaruh Komunikasi Interal Dan Komunikasi EksternalTerhadap Kinerja Karyawan(Studi Kasus pada PT. Angkasa Pura I (Persero) Bandara Adi Soemarmo Surakarta) - Cindyayana Rochmah, Reza, Ahmad Mardalis, SE, MBA (2017)
The purpose of this study are: 1) To determine the level of performance of employees at PT. Angkasa Pura I (Persero) Adi Soemarmo Surakarta; 2) To determine the effect of internal and external communications to employees performance at PT. Angkasa Pura I (Persero) Airport Soemarmo Adi Surakarta. This study uses primary data. The sample in this study were 50 respondents. The sampling technique using a simple random sampling or random sampling. The analytical method used is to test the validity, reliability test and multiple linear regression analysis with the first performed classical assumption that include normality test, multicolinearity and heterokedastisitas test. By hypothesis testing using significance together (Test-F) and partial significance test (t-test) and the coefficient of determination (R2). Results: The level of performance of employees at PT. Angkasa pura I (Persero) Surakarta is quite good; The influence of employee communication on the PT. Angkasa pura I (Persero) Surakarta is quite good; internal communications and external communications both significantly affect the performance of employees at PT. Angkasa pura I (Persero) Surakarta.